Nitrous oxide fluxes during a winter cover crop season in a Mississippi corn cropping system - Zihan Li; Dana M. Miles; Leah Hammons; Frances A. Podrebarac; John P. Brooks; Ardeshir Adeli; Renotta Smith; Joby M. Prince Czarnecki; Robert J. Moorhead; Jing Hu (Soil & Environmental Health)
Agroecosystems are the largest source of anthropogenic N2O fluxes. While cover crops (CC) offer benefits for soil health, their impacts on greenhouse gas fluxes are inconsistent. In the southeastern US, where intensive agriculture and low CC adoption are prevalent, few studies have investigated CC impact on soil N2O fluxes. Our study explored the effects of CC species and management practices on soil N2O fluxes during the winter CC growing season in Mississippi, which was conducted in a non-tilled corn cropping system with seven CC treatments. We measured in situ soil N2O fluxes, along with soil moisture and temperature, throughout the CC growing season from 2022 to 2023. Surface soil samples were also collected to analyze soil mineral nitrogen (N) content and enzyme activity. Over the study period (a total of 188 days), cumulative N2O fluxes were 0.50–1.03 ​kg N2O–N ha−1, with the lowest values from the annually-rotated Elbon rye treatment and the highest from the annually-rotated Austrian winter pea. Our results show that both CC treatments and sampling time significantly affected soil N2O fluxes. There was a strong positive correlation (r ​= ​0.34, p ​< ​0.05) between N2O fluxes and NO3–N content, which was lowest under continuous rye and rotated-rye treatments (0.31 and 0.34 ​mg ​kg−1 ). The results suggest that Elbon rye effectively reduced soil N2O fluxes during this period by lowering the soil NO3–N content, the primary substrate for denitrification. This study is one of the few studies to examine the impacts of cover crops on soil N2O fluxes in cropping systems in the southeastern US, offering insights into the cover crop effects on soil N2O fluxes during their growing season.